AN ANALYSIS OF INTERACTION PATTERNS IN THE ENGLISH WRITING CLASS - Anggita Refida Prismutitomi; Ima Isnaini Taufiqur Rohmah; Moch. Fuadul Matin (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Learning English in the classroom is closely related to how to build good interactions between the two main components, namely teachers and students. Success in the teaching and learning process is influenced by the interaction patterns of both in the classroom. This case study is aimed at determining the interaction patterns occurring in the process of English teaching-learning between the teacher and the eighth-graders at SMPN 1, Dander, Bojonegoro. The data obtained through classroom observation and interviews in two meetings of the writing class were then analyzed using the interactive model of Miles and Huberman. The findings revealed that the interaction patterns appearing in the grade 8 class consisted of group work, close-ended teacher questions, choral responses, teacher talk, student initiates teacher answers, and open-ended teacher questions. Furthermore, the results of interviews with teachers indicated that each student had different responses, and to make them active, the teacher must design the materials in an interesting and more intense way to interact continuously. The students were very enthusiastic about the way the teacher always involved students when delivering material, such as by asking questions and forming groups to solve problems. Accordingly, the interaction between teachers and students in English writing class went well and helped the students understand the material presented through the various interaction patterns they created. It is critical for English teachers to create more classroom interactions in order to encourage students to actively participate in learning activities.